Impact of perioperative blood transfusions on oncologic outcomes after radical cystectomy: A systematic review and meta-analysis of comparative studies. (September 2021) - Uysal, D.; Egen, L.; Grilli, M.; Wessels, F.; Lenhart, M.; Michel, M.S.; Kriegmair, M.C.; Kowalewski, K.F.
Abstract: This study aimed at systematically analyzing and evaluating the impact of perioperative blood transfusions (PBT) on oncologic outcomes of patients undergoing radical cystectomy for bladder cancer. This systematic review follows the recommendations of the Cochrane Handbook for Systematic Reviews and Interventions and was conducted in line with the PRISMA statement and the AMSTAR II criteria. A comprehensive database search was performed based on the PICO criteria. Two independent reviewers performed all screening steps and quality assessment. Risk of bias and certainty in evidence were assessed with the Newcastle Ottawa Scale for non-randomized trials and the GRADE approach. Of 1123 identified studies 20 were eligible for qualitative analysis and 15 for quantitative analysis reporting on 21, 915 patients. Receiving a PBT was associated with an increased risk of all-cause mortality (hazard ratio (HR) [95% confidence interval (CI)]: 1.29 [1.18, 1.40]; p < 0.001), cancer-specific mortality (HR [CI]: 1.27 [1.15; 1.41]; p < 0.001) and disease recurrence (HR [CI]: 1.22 [1.12; 1.34]; p < 0.001). Subgroup analysis of transfusion timing revealed a significantly increased risk of mortality with intraoperative or combined intra- and postoperative transfusions compared to postoperative transfusion only for all three outcomes (p < 0.001). Leukocyte-depletion was associated with increased all-cause mortality, but not cancer-specific mortality. The administration of PBT negatively impacts oncological outcomes after radical cystectomy. Therefore, careful treatment indication and strict adherence to transfusion guidelines is encouraged in order to avoid adverse effects during the perioperative course. Highlights: The administration of PBT is negatively associated with associacte oncological outcomes after radical cystectomy. Timing of transfusion may serve as a surrogate parameter for an increased risk of mortality. Leukocyte-depletion was also associated with increased all-cause, but not cancer-specific mortality in subgroup analysis.